Overexpression of FIBCD1 Is Predictive of Poor Prognosis in Gastric Cancer. Issue 6 (5th April 2018) - Jiang, Chunyi; Zhu, Jinhong; Zhou, Pengcheng; Zhu, Huijun; Wang, Wei; Jin, Qin; Li, Peng
Abstract: Objectives: Fibrinogen C domain containing 1 (FIBCD1) is a newly identified acetyl group recognition receptor. The aim of this study was to evaluate the prognostic significance of FIBCD1 in gastric cancer. Methods: This study included 706 samples, and the clinical data of all patients were recorded in detail. We studied messenger RNA (mRNA) and protein expression of FIBCD1 in cancerous and normal tissues by quantitative real-time polymerase chain reaction (n = 54) and tissue microarray immunohistochemistry analysis (n = 706), respectively. Results: mRNA and protein expression levels of FIBCD1 were significantly higher in gastric cancer than in normal tissues. High FIBCD1 protein level showed significant correlations with age ( P = .011), TNM stage ( P < .001), serum carcinoembryonic antigen (CEA) level ( P = .002), and the expression of human epidermal growth factor receptor 2 ( P < .001). Kaplan-Meier survival analysis revealed that patients with gastric cancer with high levels of FIBCD1 had a significantly shorter survival time than those with low expression levels. In univariate analysis, high FIBCD1 expression, older age, histologic type, differentiation, TNM stage, serum CEA, and serum CA19-9 level correlated with overall survival. Multivariate analysis suggested that FIBCD1 expression was an independent prognostic factor. Conclusions: FIBCD1 may be a novel biomarker to evaluate the prognosis of gastric cancer.